THE SIMULATION OF HEAT AND WATER EXCHANGE IN THE BOREAL SPRUCE FOREST BY THE LAND-SURF ACE MODEL SWAP - Gusev Y.M.; Nasonova O.N. (My University, 2003)
All previous versions of a physically based land-surface model SWAP have assumed for simplicity that vegetation is fully covered by snow during the cold season. Such assumption is reasonable only for the regions dominated by short vegetation or for warm climates where snow processes are absent. The major goals of this paper are (i) modification of the latest version of SWAP by incorporation of tall vegetation into the cold-season parameterizations to make the model applicable for simulating heat and water transfer within a boreal forest biome and (ii) validation of the modified version using the data from a forested catchment located in the boreal zone. Modification of SWAP required to parameterize radiative and turbulent exchange between the forest crown and forest floor, partitioning snowfall between interception by the canopy (in doing so, snow interception differs from rain interception) and falling to the ground, formation of snow cover on the forest crown and forest floor including snow accumulation (both in solid and liquid fractions), snow evaporation, and snowmelt. The advanced model was validated using a set of hydrometeorological data measured during 18 years (1966–1983) at the Tayozhniy catchment (covered by boreal spruce forest), Valdai, Russia. Simulations of annual and monthly snow/rain interception, daily runoff at the catchment outlet, snow density, snow depth, snow water equivalent, soil water storage in three layers (0–20, 0–50 and 0–100 cm), and monthly evapotranspiration from the catchment were compared with observations. Analysis of the results of validation shows that the new version of the model SWAP reproduces the heat and water exchange processes occurring in mid-latitude boreal forest quite reasonable.